Interpreting Bibliometric Data - Szomszor, Martin; Adams, Jonathan; Fry, Ryan; Gebert, Chris; Pendlebury, David A.; Potter, Ross W. K.; Rogers, Gordon (Frontiers in Research Metrics and Analytics, 2021)
Many academic analyses of good practice in the use of bibliometric data address only technical aspects and fail to account for and appreciate user requirements, expectations, and actual practice. Bibliometric indicators are rarely the only evidence put before any user group. In the present state of knowledge, it is more important to consider how quantitative evaluation can be made simple, transparent, and readily understood than it is to focus unduly on precision, accuracy, or scholarly notions of purity. We discuss how the interpretation of ‘performance’ from a presentation using accurate but summary bibliometrics can change when iterative deconstruction and visualisation of the same dataset is applied. From the perspective of a research manager with limited resources, investment decisions can easily go awry at governmental, funding programme, and institutional levels. By exploring select real-life data samples we also show how the specific composition of each dataset can influence interpretive outcomes.